Three new species of the leafhopper genus Thapaia Dmitriev & Dietrich (Hemiptera: Cicadellidae: Typhlocybinae) from China - Song, Yuehua; Li, Zizhong (Zootaxa, 2009)
Three new species, Thapaia tina sp. nov., T. multibudna sp. nov. and T. plumula sp. nov. from China are described and illustrated. A key to males of the genus Thapaia is provided.